Effect of Fermentation using Trichoderma harzianum and Saccharomyces cerevisiae on Crude Protein, Crude fibre and Zinc Content of Duckweed - Setiyatwan , Hendi; Harlia, E.; Rusmana, D.; Benito, Tubagus; Adriani, Lovita (International Journal of Poultry Science, 2018)
Background and Objectives: Duckweed has a potential to be used as poultry feed, however due to its high crude fibre content, its inclusion at high levels is limited. This could be overcome by means of fermentation with microbial strains like Trichoderma harzianum and Saccharomyces cerevisiae. Therefore, the present study was designed in order to improve the nutritive value of duckweed by fermentation with Trichoderma harzianum and Saccharomyces cerevisiae. Materials and Methods: There were five treatments, each having 4 replicates, thus making it a total of 20 experimental units. The treatments consisted of P1: (Fermentation using Trichoderma harzianum for 1 day followed by Saccharomyces cerevisiae fermentation for 9 days), P2: (Trichoderma harzianum for 3 days followed by Saccharomyces cerevisiae fermentation for 7 days), P3: (Trichoderma harzianum for 5 days followed by Saccharomyces cerevisiae fermentation for 5 days), P4: (Trichoderma harzianum for 7 days followed by Saccharomyces cerevisiae fermentation for 3 days) and P5: (Trichoderma harzianum for 9 days followed by Saccharomyces cerevisiae fermentation for 1 day). Results: The fermentation of Duckweed using Trichoderma harzianum and Saccharomyces cerevisiae microbes was found helpful in modifying the nutritive value of duckweed. The best combination that improved the nutritive value of duckweed in terms of increasing the crude protein (33.88%) and zinc (88.6%) content and decreasing the crude fibre (8.16%) content was P2 in which duckweed was fermented with Trichoderma harzianum for 3 days followed by Saccharomyces cerevisiae fermentation for 7 days. Conclusion: Fermentation with Trichoderma harzianum for 3 days followed by Saccharomyces cerevisiae fermentation was found effective in improving the nutrient composition of duckweed for poultry feeding.